Share to scare: technology sharing in the absence of intellectual property rights - Jos Jansen (Max Planck Institute for Research on Collective Goods, 2009)
I study the incentives of Cournot duopolists to share their technologies with their competitor in markets where intellectual property rights are absent and imitation is costless. The trade-off between a signaling effect and an expropriation effect determines the technology-sharing incentives. In equilibrium at most one firm shares some of its technologies. For similar technology distributions, there exists an equilibrium in which nobody shares. If the technology distributions are skewed towards efficient technologies, then there may exist equilibria in which one firm shares all technologies, only the best technologies, or only intermediate technologies. No other equilibria can exist.
Keywords: D82; L13; L17; O32; O34; 330; Cournot duopoly; strategic disclosure; indivisibility; innovation; trade secret; open source; skewed distribution